THE IMAGE OF AMIR TEMUR IN THE WORK OF ABDULLA ARIPOV - Kiryigitova, Nigora (FILOLOGIYA UFQLARI JURNALI, 2024)
This article is dedicated to the image of the great commander Amir Temur, the protagonist of the drama “Sokhibkiran” belonging to the hero of Uzbekistan, poet Abdulla Aripov. The article explores the image of Amir Temur as an experienced commander, a just ruler, a caring father who respects and invariably adheres to human and religious laws, and who has a unique taste, deeply understands and appreciates literature and art.